PESAN DAKWAH DALAM FILM SANG PENCERAH (SEBUAH KAJIAN AKHLAK) - Septiana, Eva; Nur, Muhammad; Sabdo, Sabdo (Universitas Muhammadiyah Metro, 2021)
Films have a major contribution in shaping civilization because they can have a major influence on the human psyche. The effect of power of a film is an advantage and a weakness that cannot be denied. Films function as a transmission of values because people can be influenced by what they see from the film. In this context, people's behaviour that deviates from Islamic values needs to be enlightened. So, a film that has enlightening values and da'wah messages which can invite and provide guidance to the community to do goodis needed. Films that contain historical value can provide insight and enlightenment on the conditions that occur in society. That film is the film of Sang Pencerah. This film tells the story of K.H Ahmad Dahlan's struggle to straighten the beliefs of the Kauman people who practice polytheism. In addition, when he was still quite young, Ahmad Dahlan, with his knowledge of Falaq, who felt uneasy about the practice of praying that was deviating, which did not lead straight to the Ka'bah, moved his heart to take action by changing the direction of the Kauman Mosque qibla. However, this action actually triggered the anger of Kyai Penghulu Kamaludiningrat who is a kyai who keeps the tradition. Accompanied by his wife Siti Walidah and the support of his five loyal students named Fahrudin, Sudja, Sangidu, Hisyam and Dirjo, Ahmad Dahlan formed the Muhammadiyah organization to strengthen and expand his preaching area. Based on the above background, the researchers formulated the following problems: What is the message of the da'wah in the film of Sang Pencerah and how is the technique of delivering the message in the film of Sang Pencerah. The research of the film of Sang Pencerah aims to determine the contents of the da'wah messages and the techniques of delivering the messages. In interpreting a film, an appropriate research methodology is needed so that later it can reveal the hidden meanings behind the signs in the film. The author uses a qualitative methodology with a descriptive research specification that focuses on semiotic analysis. Based on the data that has been researched, the results of the study show that the message of the da'wah in the film of Sang Pencerah is Akhlak. Moral messages cover the areas of morals towards family and morals towards others.